Gibbs energy function: Difference between revisions
Jump to navigation
Jump to search
Carl McBride (talk | contribs) mNo edit summary |
Carl McBride (talk | contribs) mNo edit summary |
||
Line 2: | Line 2: | ||
:<math>\left.G\right.=A+pV</math> | :<math>\left.G\right.=A+pV</math> | ||
:<math>\left.G\right.=U-TS+pV</math> | :<math>\left.G\right.=U-TS+pV</math> | ||
Line 16: | Line 15: | ||
thus one arrives at | thus one arrives at | ||
:<math>\left.dG\right.=-SdT+Vdp</math> | |||
<math>\left.dG\right.=-SdT+Vdp</math> | |||
For ''G(T,p)'' we have the following ''total differential'' | For ''G(T,p)'' we have the following ''total differential'' | ||
:<math>dG=\left(\frac{\partial G}{\partial T}\right)_p dT + \left(\frac{\partial G}{\partial p}\right)_T dp</math> | :<math>dG=\left(\frac{\partial G}{\partial T}\right)_p dT + \left(\frac{\partial G}{\partial p}\right)_T dp</math> |
Revision as of 18:12, 22 February 2007
Definition:
Taking the total derivative
From the Second law of thermodynamics one obtains
thus one arrives at
For G(T,p) we have the following total differential